Nanotechnology‐Assisted Immunoengineering for Cancer Vaccines. Issue 1 (27th November 2022) - Mamuti, Muhetaerjiang; Chen, Weizhi; Jiang, Xiqun
Abstract : Recently, approaches based on nano‐immunoengineering have been developed to optimize the potency of vaccines while minimizing toxicity. To achieve desirable immune responses, vaccines should be able to traffic into lymph nodes (LN) and provide antigen and inflammatory signals for a sufficient temporal duration, to activate the desired cellular and humoral immunity. In that case, the application of nanotechnology in vaccine design provides the possibility of co‐delivering of antigen and adjuvants to the targeted organs, tissues, cells, or even intracellular compartments at the determined time to optimize the qualities of immune responses. Herein, the recent advances on nanovaccine design, including a brief summary of natural and synthetic biomaterials for antigen and adjuvant packing, are reviewed. The emerging approaches for regulating pharmacokinetics of vaccines will be further discussed especially for LN targeting as well as antigen uptake by antigen‐presenting cells. Those advances provide a prospect of shaping immune response by immunoengineering‐based nanovaccines. Abstract : Utilizing nano‐immunoengineering approaches to potentiate the potency, quality, and durability of vaccine response is an effective strategy and also a great task. Herein, the current development on the design strategies of nanovaccines, especially from the aspect of improving vaccine pharmacokinetics to provide a theoretical guideline for exploiting novel nanovaccines to bolster immune responses, is summarized.